Sleep disorders and relationship with comorbid anxiety and depression in carpal tunnel syndrome - Çevik Yurtoğulları, Şükran; Seferoglu, Meral (The European Research Journal, 2021)
Objectives: In this study, it was aimed to assess relationship of disease severity with sleep quality, depression and anxiety in patients with carpal tunnel syndrome (CTS) and to compare findings with healthy controls. Methods: The study included 35 patients diagnosed as CTS and 20 healthy individuals. In CTS patients, symptom severity and functional disorders were assessed using Boston Carpal Tunnel Questionnaire (BTCQ). The sleep quality was assessed using Pittsburg Sleep Quality Index (PSQI) in CTS patients and healthy controls. The Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI) were used to evaluate depression and anxiety accompanying to CTS and sleep disorder. Results: In the assessment of general sleep quality, it was found that PSQI scores were significantly higher in CTS group when compared to healthy controls (p < 0.0001). Again, the BDI and BAI scores were also significantly higher in CTS group than control group (p < 0.0001 and p < 0.003, respectively). There was a strong, positive correlation between BTCQ symptom severity scale (SSS) and PSQI (r = 0.774; p < 0.0001). A significant, positive correlation was observed between Boston SSS and BDI scores (r = 0.666; p < 0.001). When assessed correlation between anxiety scores and Boston SSS and functional state scale (FSS), it was found that anxiety was increased by increasing severity of CTS, indicating a positive, moderate correlation (r=0.469, p < 0.0001 and r=0.464, p < 0.0001). Conclusions: The pain in patients with CTS can impair sleep quality, which, in turn, may increase risk for depression and anxiety. Thus, comorbid psychiatric symptoms and signs should be considered in the treatment of patients with CTS.